Whole-Genome Sequencing of ST2 A. baumannii Causing Bloodstream Infections in COVID-19 Patients - Sabrina Cherubini; Mariagrazia Perilli; Bernardetta Segatore; Paolo Fazii; Giustino Parruti; Antonella Frattari; Gianfranco Amicosante; Alessandra Piccirilli (MDPI AG, 2022)
A total of 43 A. baumannii strains, isolated from 43 patients affected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and by bacterial sepsis, were analyzed by antimicrobial susceptibility testing. All strains were resistant to almost three different classes of antibiotics, including carbapenems and colistin. The whole-genome sequencing (WGS) of eight selected A. baumannii isolates showed the presence of different insertion sequences (ISs), such as ISAba13, ISAba26, IS26, ISVsa3, ISEc29, IS6100 and IS17, giving to A. baumannii a high ability to capture and mobilize antibiotic resistance genes. Resistance to carbapenems is mainly mediated by the presence of OXA-23, OXA-66 and OXA-82 oxacillinases belonging to OXA-51-like enzymes. The presence of AmpC cephalosporinase, ADC-25, was identified in all A. baumannii. The pathogenicity of A. baumannii was exacerbated by the presence of several virulence factors. The multi-locus sequence typing (MLST) analysis showed that all strains belong to sequence type 2 (ST) international clone.